Developments in comparative employment relations in Australia and New Zealand: reflections on 'Accord and Discord'. (2nd January 2018) - Bray, Mark; Rasmussen, Erling
ABSTRACT: This article reflects on the recent literature comparing employment relations in Australia and New Zealand. It begins by returning to the 'Accord and Discord' article by Bray and Walsh, published in this journal in 1995, and the wave of comparative analysis that surrounded it. Developments since then, in both the real world of Australian and New Zealand employment relations and theoretical debate, are reviewed. They suggest two trends in comparative analysis. First, there is a need to go beyond institutionalist analysis in exploring the similarities and differences between the two countries. Second, it is possible that trends in Australian and New Zealand employment relations should be located in wider trajectories towards neoliberalism. Both trends offer great potential for future research.